First Identification of Late Permian Nb‐Enriched Basalts in Ailaoshan Region (SW Yunnan, China): Contribution From Emeishan Plume to Subduction of Eastern Paleotethys. Issue 5 (13th March 2019) - Xu, Jian; Xia, Xiao‐Ping; Lai, Chun‐Kit; Zhou, Meiling; Ma, Pengfei
Abstract: Interactions between ocean plate subduction and the nearby mantle plume represent a possible major drive for mantle heterogeneity. We first report Late Permian ( 261 Ma) Nb‐enriched basalts (NEBs) in the Ailaoshan region. The Ailaoshan NEBs are characterized by high Nb (10.1–11.5 ppm) and Nb/La (1.2–1.3), positive Nb‐Ta anomalies and ε Nd( t ) (+5.65 to +6.21), and low and mantle‐like zircon δ 18 O (5.28–5.75‰). Our results demonstrate that the source region contains an enriched mantle component, which may have derived from the nearby Emeishan plume. The Ailaoshan NEBs were possibly generated by mixing of subduction‐derived, mid‐ocean ridge basalt (MORB)‐like components and mantle plume‐derived, enriched components. We suggest that the Late Permian rollback of the Ailaoshan oceanic slab may have entrained the Emeishan plume material into the subduction zone, which caused compositional heterogeneity in the mantle wedge and formed the Ailaoshan NEBs. Plain Language Summary: The plume‐subduction interaction is a special and very important event in the modern history of our planet Earth. Such interaction could be one of the major mechanisms for present mantle heterogeneity. As for the behavior of mantle plumes near ancient subduction zones is still a mystery. The Paleo‐Tethyan Ailaoshan Ocean may have experienced late Paleozoic subduction beneath the South China Block, which may be influenced by the Emeishan mantle plume to the east. However, volcanic arc rocks outcropped in the subduction zone tended to be metasomatized by the subduction components, which made it difficult to trace their source compositions. We have recently identified the Late Permian Nb‐enriched basalts in the Ailaoshan region, which have little subduction component inheritance. The bulk‐rock geochemical, Sr‐Nd and zircon O isotopic data indicate that the Emeishan plume‐derived enriched component existed in their source region. Considering the Permian regional extension in South China Block, we suggest that the Ailaoshan oceanic slab rollback‐induced counterflow drove westward flow of Emeishan plume material resulted in the entrainment of enriched component around the subduction zone. This study implies that the ancient plume‐subduction interaction may have played an important role in the mantle heterogeneity. Key Points: Ailaoshan Nb‐enriched basalts ( 261 Ma) were formed coeval with Emeishan plume activity The basaltic magma may have generated by mixing between depleted MORB‐type and enriched Emeishan plume mantle components Ailaoshan oceanic slab rollback may have driven the entrainment of Emeishan plume material into the mantle wedge above the subducted slab